x2-8x=48

Move 48 to the left side of the equation by subtracting it from both sides.

x2-8x-48=0

Consider the form x2+bx+c. Find a pair of integers whose product is c and whose sum is b. In this case, whose product is -48 and whose sum is -8.

-12,4

Write the factored form using these integers.

(x-12)(x+4)=0

(x-12)(x+4)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

x-12=0

x+4=0

Set the first factor equal to 0.

x-12=0

Add 12 to both sides of the equation.

x=12

x=12

Set the next factor equal to 0.

x+4=0

Subtract 4 from both sides of the equation.

x=-4

x=-4

The final solution is all the values that make (x-12)(x+4)=0 true.

x=12,-4

Solve for x x^2-8x=48